PENGARUH STRUKTUR MODAL TERHADAP AGRESIVITAS PAJAK DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Hamdi, Syaibatul (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The purpose of this research is to know how big influence of capital structure to tax aggressiveness. In addition, this study also examined the moderating role of profitability for the effect of capital structure on tax aggressiveness. The research was conducted on consumer goods sector manufacturing companies listed in Indonesia Stock Exchange. The type of this research is quantitative research, while the sampling technique is done by using purposive sampling method. The sample of this research is 8 companies period of year 2011-2015. The independent variable in this research is Capital Structure. Then the dependent variable in the form of Tax Aggressiveness and Moderation Variable is Profitability. The analytical method used is classical assumption test method, linear regression, t test analysis, f test analysis, and path analysis using computer program SPSS version 22.0 and Microsoft Excel 2010. Based on the results of research conducted, pointed out that partially capital structure effect on aggressiveness taxes, and profitability moderate the effect of capital structure on tax aggressiveness